Gestão de resíduos sólidos e a integração de catadores em cidades pequenas: os casos de Assis Chateaubriand e Palotina, PR - Costa, Adrielly Grava (2017)
Solid waste recycling is an imperative that seeks not only to generate value, but also to reduce the use of natural resources and avoid damages to the environment. Waste collectors are social actors relevant to the recycling process, since they are low-cost labor for the recovery of recyclable materials, although their service on the streets is susceptible to a series of risk and health problems. When organized in associations or cooperatives, collectors try to reduce problems and become new partners for the cities. This partnership is an alternative in the management of solid residues, since they help in the process of using recycling material, increasing the work and reducing the flux of residues to landfills. The cities selected for this study, Assis Chateaubriand and Palotina, both in the state of Parana in Brazil, have similar characteristics, like the population and economy, but they have different experiences in solid residues management. Both are considered small cities and have collectors organized in partnerships with the government for the selection of recycling residues. This research aims to analyze how the government integrates the collectors in order to develop the management of those residues, comparing the cases of both cities. The methodology used was the documentary observation, the data collection, interviews and field observation, which enabled the analysis and assessment to the way that the government can meet the legal requirement of the integration of collectors in the management of solid residues specifically in the analyzed cities. This study intended to contribute for the developing of studies about the urban environment, small towns and garbage collectors.